2001
DOI: 10.1177/107769900107800102
|View full text |Cite
|
Sign up to set email alerts
|

The Spiral of Silence and Public Opinion on Affirmative Action

Abstract: This study sought to more fully explicate the key variables involved in Noelle-Neumann's spiral of silence theory, which states that fear of isolation keeps individuals from expressing opinions perceived to be in the minority. We tested the theory in the context of public discussion about affirmative action policies, a domain seemingly ideal due to its moral and value-laden characteristics. Data from 217 randomly selected adults in October 1998 indicate that fear of isolation indeed prevents one from publicly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 4 publications
7
118
0
4
Order By: Relevance
“…Scholars note how forming an opinion on a public issue is a process, not something that is straightforward or taken-for granted. Indeed, people form opinions in interactions and dialogues with others and engagement with media (Christen & Gunther, 2003;Eveland & Scheufele, 2001;Hoffman et al, 2007;Huckfeldt & Sprague, 1995;Moy, Domke & Stamm, 2001). In this way, scholars note that processes of communication are important in forming an opinion about a public issue, which is why we address whether people discuss gay rights (Hypothesis 3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars note how forming an opinion on a public issue is a process, not something that is straightforward or taken-for granted. Indeed, people form opinions in interactions and dialogues with others and engagement with media (Christen & Gunther, 2003;Eveland & Scheufele, 2001;Hoffman et al, 2007;Huckfeldt & Sprague, 1995;Moy, Domke & Stamm, 2001). In this way, scholars note that processes of communication are important in forming an opinion about a public issue, which is why we address whether people discuss gay rights (Hypothesis 3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu & Fahmy, 2011;Moy et al, 2001;Perry & Gonzenbach, 2000). We are, however, interested in variations between the private and the public sphere, and therefore expand this approach by studying variations between the private and the public opinion climates.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Another question concerns the impact of the general, abstract public as compared to the impact of peers and relevant reference groups. Several studies have shown that opinions held by family and friends are more important when deciding whether to speak out (Glynn & Park, 1997;Krassa, 1988;Moy, Domke & Stamm, 2001).…”
Section: Spiral Of Silence and The Opinion Climate: Our Approachmentioning
confidence: 99%
See 2 more Smart Citations